Ejaculate for Microbiological Culture: To Wash or Not To Wash? - Tom Theiler; Ioana Diana Olaru; Charlotte Kilzer; Franziska Schuler; Frieder Schaumburg (Microbiology Spectrum, 2022)
ABSTRACT Bacteria can be associated with male infertility. Antibacterial substances (e.g., zinc-containing proteins, antimicrobial peptides) in ejaculates might impair the growth of bacteria in culture. We therefore wanted to test if removing antibacterial substances by washing the ejaculate could improve the detection of bacteria in culture. All ejaculates from patients ≥18 years old, which were obtained for routine diagnostics to assess male infertility were included in this study (no exclusion criteria were applied). Test samples were diluted with 2 mL sterile 0.45% saline, vortexed, and centrifuged (5 min; 7.5 × g). After the removal of 2 mL of the supernatant and resuspension, 10 μL of the pellet was used for aerobic and anaerobic culture. Control samples were cultured identically but without washing. Species identification was done with matrix-assisted laser desorption ionization–time of flight mass spectrometry. A total of 186 samples were included. The data set was stratified into five groups (Gram-negative rods [GNR], anaerobes [AN], Enterococcus spp. [EC], coagulase-negative staphylococci [CNS], and viridans streptococci [VS]). Compared to the control arm, the test arm revealed significant lower proportions for CNS (59.1% versus 44.6%, P < 0.01) and VS (53.8% versus 41.9%, P = 0.03). Similarly, slightly lower proportions of GNR (16.1% versus 15.1%, P = 0.89), AN (19.9% versus 17.2%, P = 0.5), and EC (25.3% versus 23.1%, P = 0.63) were observed. The medians of CFU were lower in test samples compared to the control samples (6.5 × 103 versus 2.5 × 103, P < 0.01) for any bacterial growth. Lower colony counts were also observed for individual bacterial groups. In conclusion, preculture washing of ejaculates results in a decrease in total bacteria count and culture-positive samples. IMPORTANCE This study compares two methods for processing ejaculate samples from men undergoing investigations for infertility. The method of sample washing and centrifugation was compared to the standard method of direct inoculation and culture. The study hypothesis was that preprocessing of samples may increase bacterial yield by removing bactericidal substances from semen. However, we found that washing ejaculate samples before microbiological culture did not improve the detection of bacteria and led to a reduction in colony counts.